Loading of the medial meniscus in the ACL deficient knee: A multibody computational study. (March 2017) - Guess, Trent M.; Razu, Swithin
Highlights: Loss of anterior crucial ligament (ACL) constraint increased medial meniscus posterior horn loading four fold with application of anterior tibial force. For the intact knee, applying a combined anterior tibial force plus external tibial torque produced the greatest loading on the medial meniscus. The peripheral meniscal attachments of the deep medial collateral ligament help constrain posterior medial meniscal motion, increasing hoop tension in the posterior horn. Abstract: The menisci of the knee reduce tibiofemoral contact pressures and aid in knee lubrication and nourishment. Meniscal injury occurs in half of knees sustaining anterior cruciate ligament injury and the vast majority of tears in the medial meniscus transpire in the posterior horn region. In this study, computational multibody models of the knee were derived from medical images and passive leg motion for two female subjects. The models were validated against experimental measures available in the literature and then used to evaluate medial meniscus contact force and internal hoop tension. The models predicted that the loss of anterior cruciate ligament (ACL) constraint increased contact and hoop forces in the medial menisci by a factor of 4 when a 100 N anterior tibial force was applied. Contact forces were concentrated in the posterior horn and hoop forces were also greater in this region. No differences were found in contact or hoop tension between the intact and ACL deficient (ACLd) knees when only a 5 Nm external tibial torque was applied about the long axis of the tibia. Combining a 100 N anterior tibial force and a 5 Nm external tibial torque increased posterior horn contact and hoop forces, even in the intact knee. The results of this study show that the posterior horn region of the medial meniscus experiences higher contact forces and hoop tension, making this region more susceptible to injury, especially with the loss of anterior tibia motion constraint provided by the ACL. The contribution of the dMCL in constraining posterior medial meniscus motion, at the cost of higher posterior horn hoop tension, is also demonstrated.